2021
DOI: 10.1016/j.canlet.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PP2A with lomitapide suppresses colorectal tumorigenesis through the activation of AMPK/Beclin1-mediated autophagy

Abstract: BackgroundColorectal cancer (CRC) is one of the most malignant cancer worldwide, and the limited e cacy of existing treatments is the leading cause of death in patients with CRC. Thus, novel drugs for CRC treatment are urgently needed. MethodsWe screened an FDA-approved small-molecule library upon HCT116 cells, and identi ed lomitapide as a novel CRC anticancer compound. Then we con rmed the activities of lomitapide on CRC cells by WST-1 assay, colony formation, and ow cytometry. RNA sequencing and GO analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…6E ), which validates the lomitapide-mediated activation of autophagy system. During the preparation of this manuscript, Zuo et al reported that lomitapide plays a role in the control of cancer cell death [ 41 ], which is consistent with our findings. These authors reported that lomitapide suppresses the dephosphorylation of AMPK by directly inhibiting protein phosphatase 2 A (PP2A).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…6E ), which validates the lomitapide-mediated activation of autophagy system. During the preparation of this manuscript, Zuo et al reported that lomitapide plays a role in the control of cancer cell death [ 41 ], which is consistent with our findings. These authors reported that lomitapide suppresses the dephosphorylation of AMPK by directly inhibiting protein phosphatase 2 A (PP2A).…”
Section: Resultssupporting
confidence: 91%
“…These findings support the therapeutic advantages of lomitapide over other mTOR inhibitors. In light of our results and Zuo et al’s report [ 41 ], we believe that lomitapide’s superior anticancer activity can be achieved by targeting multiple autophagy signaling hubs including mTORC1 and PP2A.…”
Section: Discussionsupporting
confidence: 78%
“…LiP‐SMap is a reliable technique to identify target proteins of drugs. [ 16 ] In this study, RanBP3 was identified as a direct target of NU2058. RanBP3 is a RanGTP‐binding protein that has been reported to enhance nuclear export of active β ‐catenin, independent of its role as a CRM1‐associated nuclear export cofactor.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, activated AMPK also phosphorylates downstream tuberous sclerosis complex 1 and 2 (TSC1/2) to enhance inhibition of Rheb, thereby inhibiting mTOR and inducing autophagy ( 19 ). In HCT116 and HT29 human CRC cells, knockdown of AMPK restricted tumor autophagy-dependent cell death, leading to tumor progression ( 20 ) ( Figure 1 ).…”
Section: Crucial Pathways For Autophagy Regulation In Crcmentioning
confidence: 99%
“…In addition to natural products, there are several repositioning small-molecule compounds that contribute to CRC therapy via modulating autophagy. For instance, lomitapide, a clinical drug approved by the Food and Drug Administration (FDA) for the treatment of hypercholesterolemia, is recently reported to upregulate AMPK phosphorylation and promote the formation of BECN1-VPS34-ATG14 complex, thereby inducing autophagy in HCT116 and HT29 human CRC cells, which significantly inhibits tumor proliferation in vitro and in vivo ( 20 ). Similarly, flubendazole, an anthelmintic drug approved by FDA, downregulates STAT3 phosphorylation levels, mTOR and p62, and upregulates Beclin 1 and LC3-I/II in HCT116, RKO and SW480 human CRC cells, which promoting the initiation of autophagy to prevent tumor progression without substantially affecting normal cell proliferation ( 38 ).…”
Section: Therapeutic Strategies Targeting Autophagy For Crc Therapymentioning
confidence: 99%